Introductory Remarks by Scott Anderson. (2019) - Anderson, Scott
Abstract : Over the past two years, we have really seen the Trump administration make treaty withdrawal something of a signature move, from the Treaty of Amity with Iran to the Intermediate-Range Nuclear Forces Treaty, to the Optional Protocol for the Vienna Convention on Diplomatic Relations. The administration has taken steps to remove the United States, rightly or wrongly, from a wide array of longstanding international legal obligations. And while it is far from unprecedented, the administration has done so at a little bit of a faster pace than certain prior administrations have—and has embedded a lot of these moves within a consistent critique of international institutions and international commitments that promises further change on the horizon.